The Mediating Role of Student Attitude in Socratic Mathematics Instruction and Achievement: Evidence from 9493 Learners in Vietnam and Cambodia - Amin, Abdul; Andriyati, Nofica; Hussain, Amil; Chen, Yue (Innovations in Pedagogy and Technology, 2026)
Large disparities in mathematics achievement persist across Southeast Asia, raising questions about how instructional practices interact with students’ attitudes to shape learning outcomes in contrasting educational systems. Using data from 9493 fifteen-year-old students in Vietnam and Cambodia drawn from Programme for International Student Assessment (PISA) 2022, this study examines the relationships among Socratic mathematics instruction (SMI), student mathematics attitude (SMA), and student mathematics performance (SMP). Structural equation modeling was employed to compare a high-performing system (Vietnam) with a lower-performing one (Cambodia) and to assess the mediating role of student attitudes in translating instructional practices into achievement. Across both countries, SMI was positively associated with SMA (Vietnam: β = 0.43; Cambodia: β = 0.39; p < 0.001), and SMA was positively related to SMP, with a markedly stronger association in Cambodia (β = 0.28) than in Vietnam (β = 0.07; p < 0.001). The direct association between SMI and performance was positive in Vietnam (β = 0.08, p < 0.001) but small and negative in Cambodia (β = −0.01, p = 0.004). Mediation analysis revealed that the indirect effect of SMI on performance through SMA was substantially larger in Cambodia (β = 0.11) than in Vietnam (β = 0.03; p < 0.001), indicating that student attitudes play a compensatory role in contexts with limited instructional capacity. These findings highlight SMA as a key mechanism through which SMI affects achievement and show that instructional effectiveness is context dependent. By integrating pedagogical, affective, and contextual factors, the study extends Expectancy-Value Theory and emphasizes aligning instructional reforms with students’ motivational and attitudinal profiles, especially in resource-constrained settings.